DECONSTRUCTING ACADEMIC THOUGHT: MAPPING RESEARCH IN ISLAMIC SOCIAL FINANCE THROUGH BIBLIOMETRIC APPROACH AND LITERATURE REVIEW - Khairunnisa, Khairunnisa (Proceeding International Seminar of Islamic Studies, 2024)
This article delves into the intricate landscape of academic discourse within Islamic social finance, employing a dual methodology of bibliometric analysis and comprehensive literature review. Through a meticulous examination of scholarly publications, the study endeavors to deconstruct the prevailing paradigms and trends shaping research in this field. By employing bibliometric techniques, it maps the quantitative aspects of research topics and emerging themes. Overall, this study contributes to a deeper understanding of Islamic social finance and underscores its relevance in addressing contemporary societal issues.